Leptin Methylation and mRNA Expression Associated With Psychopathology in Schizophrenia Inpatients - Song, Jiaqi; Chen, Yan; Zhao, Qing; Li, Hongna; Li, Wei; Chen, Ke; Yu, Jianjin; Fu, Weihong; Chen, Dachun (Frontiers in Psychiatry, 2022)
Leptin involved in the regulation of dopaminergic neurons of the central nervous system may confirm the hypothesis of neurodevelopment in schizophrenic patients. However, specific genetic mechanisms are undefined. Therefore, we aimed to explore the regulation of DNA methylation of leptin promoters and mRNA expression in patients with schizophrenia. A cross-sectional study enrolled 40 patients and 40 healthy controls from the Beijing Huilongguan Hospital in China. The leptin methylation levels and mRNA expression were examined by highly sensitive mass spectrometry based on the MassARRAY System and real-time quantitative polymerase chain reaction (qPCR). The Positive and Negative Symptoms Scale (PANSS) was applied to estimate the clinical symptoms of patients. The LEP-CpG7 and CpG15 methylation in patients were significantly higher than in healthy controls (P < 0.05). The LEP-CpG11, CpG33.34.35, CpG36 methylation, and mRNA expression decreased significantly in patients compared with healthy controls (P < 0.05). After controlling gender, age, BMI, dose of antipsychotic and duration of illness, LEP-CpG7 methylation was negatively associated with PANSS positive symptoms subscore (r = −0.485, P = 0.005). In addition, LEP-mRNA expression was negatively correlated with PANSS total score (r = −0.385, P = 0.03) and positive subscale (r = −0.392, P = 0.026). Nevertheless, only the LEP-CpG7 methylation level remained negatively correlated to the PANSS positive subscore following multiple stepwise regression (β = −-17.071, P = 0.037). These results suggest that leptin methylation and mRNA expression might contribute to the pathogenesis of schizophrenia. LEP-CpG7 methylation may be negatively associated with positive symptoms in patients with schizophrenia